European Religious Cultures Essays offered to Christopher Brooke on the occasion of his eightieth birthday - Rubin, Miri (IHR Shorts, 2020)
European Religious Cultures is a set of stimulating essays first written as offerings for Christopher Brooke on his eightieth birthday. They are now gathered for the enjoyment of all those interested in the history of religious cultures. They address a variety of practices in religious life -- among them pilgrimage and the urban cult of saints, the monastic performance of liturgy, the choice to enter the priesthood -- and situate them within the life-cycles and social relations of medieval Europeans. The authors have been inspired by Christopher Brooke's own interests over a long and fruitful career. First published in 2008, European Religious Cultures is now reissued as an Open Access edition with a new introduction by Professor Miri Rubin.